Characterizing ProstivaTM RF Treatments of the Prostate for BPH with Gadolinium-Enhanced MRI. (2009) - Huidobro, Christian; Larson, Benjamin; Mynderse, Samuel; Myers, James J.; Busel, David; Acevedo, Cristian; Larson, Thayne R.; Mynderse, Lance A.
Abstract : Transurethral needle ablation (TUNA) is an accepted and effective therapy for the treatment of lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH). Prostiva TM (Medtronic, Shoreview, MN) is the newest-generation device, which includes a new needle design and radio frequency (RF) generator. This device creates temperatures of 120°C and necrotic lesions in less than 2.5 min. Using previously described techniques, we analyzed dynamic, gadolinium-enhanced MRIs to characterize the ablative properties of the new Prostiva TM RF device. Ten men with LUTS due to BPH were treated with the standard Prostiva TM manufacturer–recommended protocol. The bladder neck and lateral lobes received treatment based on prostate volume and prostatic urethral length. Gadolinium-enhanced MRI sequences were obtained prior to and 1 week post-treatment. Analyze® software (Mayo Clinic Biomedical Imaging Resource, Rochester, MN) was used to evaluate MRIs. New gadolinium defects were seen in all patients following Prostiva TM treatments. All lesions coalesced within the prostate. No defects were seen beyond the prostate, and the urethra was spared in all patients. The mean volume of necrosis was 7.56 cc, representing a mean of 11.28% of total prostate volume. Dynamic, gadolinium-enhanced MRIs demonstrate new vascular defects representing necrosis caused by Prostiva TM RF therapy of the prostate. The standard Prostiva TM RF protocol produces lesions that coalesce to create larger lesions in the bladder neck and lateral lobes. Compared to the TUNA® Precision Plus TM device, the ablative lesions appear comparable while produced with a shorter burn time.